Imam Al-Zuhri's Reading in IbnAtiyah's Interpretation (Surat Al-Baqara): Collection and a Study (Islamic Sciences Journal, 2024)
Praise be to Allah, the Lord of the worlds, and prayers and peace be upon the Master of Messengers, our Prophet Muhammad, may Allah bless him and grant him peace. The science of Quranic readings is one of the most honorable sciences. Peace be upon him, which I read to the Messenger in seven letters to ease the suffering of this nation, and the Prophet, may Allah’s prayers and peace be upon him, taught it to the honorable companions, may Allah  pleased  them, and  the companions taught to the followers, and then the followers of the followers until the matter ended with the ten readers.      I have shown in this research that the readings that the reader reads was used by Imam Al-Zuhri, especially in Surat Al-Baqarah, and showed the correct ones and the abnormal ones, as a service from us to this dear book, and Allah is the Grantor of success.
Keywords: Reading, Al-Zuhri, interpretation, Ibn Attia, meanings.